2010
DOI: 10.1002/jsfa.4021
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in content, chemical composition and antimicrobial and cytotoxic activities of essential oils from four Mentha species

Abstract: Of the Mentha essential oils tested, M. arvensis essential oil showed relatively better antimicrobial and cytotoxic activities. A significant variation in the content of most of the chemical components and biological activities of seasonally collected samples was documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
194
6
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(246 citation statements)
references
References 22 publications
19
194
6
5
Order By: Relevance
“…The essential oil of the peppermint (Mentha piperita L. (Lamiaceae)) has high antimicrobial potential against phytopathogens Aspergillus flavus and A. niger (HUSSAIN et al, 2010). The antimicrobial action of the oils from the neem (Azadirachta indica A. Juss.…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil of the peppermint (Mentha piperita L. (Lamiaceae)) has high antimicrobial potential against phytopathogens Aspergillus flavus and A. niger (HUSSAIN et al, 2010). The antimicrobial action of the oils from the neem (Azadirachta indica A. Juss.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies reported a small MIC ranging from 0.21 ± 0.01mg/ml, 0.345 ± 0.01mg/ml to 0.349 ± 0.008 mg/ml against E. coli. 18,24 Likewise, Martins et al 22 showed the MIC values ringing from 250 µg/ml to 500 µg/ml against E. coli, Salmonella enteritidis and Klebsiella pneumonia. The lowest value of MIC < 3.5μg/ml was reported by Sarer et al 36 M. spicata essential oil was detected as active against only Klebsiella spp.…”
Section: Resultsmentioning
confidence: 99%
“…23 The difference in yield can be attributed to the harvest season of the plant when a high essential oil yield was seen in summer (when the plants were in full bloom) than in winter (when the plants reached the end of their growing cycle). 7,24,25 The composition of essential oils of M. spicata is presented in table 1. One hundred and sixteen compounds were identified accounting for 99.92% of the total amount.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, these compounds determine the biological properties of the oils 25 . The chemical composition of plants can be subject to quantitative and qualitative variation, however biological activity is similarly subject to variation 36,37,38 . In this study A. spinosa was collected in the same place but at different times and years, however, in the same period spring summer of southern hemisphere.…”
Section: Resultsmentioning
confidence: 99%